Analisis Kepatuhan Dalam Implementasi Kerjasama Indonesia-Tiongkok Menangani Kasus Penyelundupan Narkoba Melalui Jalur Laut Pada Tahun 2012-2015 - Wardani, Ella Aditya; Utomo, Tri Cahyo; Wahyudi, Fendy Eko (Journal of International Relations, 2018)
The higher number of drugs users in Indonesia, indicated that drugs smuggling inIndonesia is also increasing. The paths that used by drug traffickers also change by seabecause the sea lane is considered a safe path and can generate more profits compared toother routes. One of the biggest drugs suppliers in Indonesia is China. Therefore, both theGovernment of Indonesia and the Chinese Government agreed to create a cooperation thatis contained in the form of a Memorandum of Understanding. This study analyzed how thecompliance of Indonesia and China in running the Memorandum of Understanding that hasbeen formed in dealing with cases of drugs smuggling through the sea. The author will usethe theory of compliance from Ronald B. Mitchell and seen from the point of view ofIndonesia because Indonesia is a destination country of drugs smugglers from China. Acompliance is closely related to the effectiveness of a form of cooperation. The compliancehere will be measured based on the implementation of the MoU. Indicators of theimplementation are seen from the outputs, outcomes, and impacts of the cases raised.